Modulators of Oxidative Stress Chemical and Pharmacological Aspects - Saso, Luciano; Gurer-Orhan, Hande; Stepanić, Višnja (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book starts with the editors' preface summarizing the contributions of each of the following thirteen articles dealing with chemical and pharmacological aspects of the molecular modulators of the oxidative stress in regard to various therapeutic approaches in cardiovascular and neurodegenerative diseases, cancer, and diabetes. The seven articles present data from original research studies enlightening the roles and mechanisms of action of small molecular weight compounds (natural and synthetic; ascorbic acid/vitamin C, deferoxamine, N-acetylcysteine, MitoVitE, α-tocopherol, trolox, and ezetimibe) or proteins (SIRT3) in modulation of oxidative stress. In the six review papers, the authors present and discuss the possible therapeutic potential of novel approaches and compounds that are promising and deserve further investigation, in modulation of oxidative stress.